Effect of hydrodynamic heterogeneity on micromixing intensification in a Taylor–Couette flow reactor with variable configurations of inner cylinder - Liu, Lu; Yang, Xiaogang; Yang, Jie; Li, Guang; Guo, Yanqing (2021)
Effect of hydrodynamic heterogeneity on micromixing intensification in a Taylor–Couette flow (TC) reactor with variable configurations of inner cylinder has beeninvestigated by adoption of a parallel competing iodide-iodate reaction system. Twotypes of inner cylinder, circular inner cylinder and lobed inner cylinder (CTC andLTC), were used to generate hydrodynamic heterogeneity, focusing on the effects ofthe Reynolds number, the acid concentration, and the feeding time on the micro-mixing performance. Segregation index (Xs) was employed to evaluate the micro-mixing efficiency. It is revealed thatXs decreases with the increase of Reynoldsnumber and feeding time but increases with the increase of acid concentration forboth the CTC and LTC. However, the LTC does present a better micromixing perfor-mance at various operating conditions than that of the CTC as affirmed by both theexperimental and computational fluid dynamics simulation results.